Contribution to the knowledge of the genus Acrophyma Bergroth, 1917 (Hemiptera: Heteroptera: Acanthosomatidae) - Faúndez, Eduardo I. (Zootaxa, 2009)
Acrophyma cumingii (Westwood, 1837) n. comb. is revalidated and redescribed, the new synonymy A. cumingii = A. impluviata (Blanchard, 1852) is proposed; also given are new Chilean records and the first host plant information on Nothofagus dombeyi (Mirb.) Oerst. (Nothofagaceae) for A. cumingii, a new Brazilian record for A. bicallosa (Stål, 1872), and a species-list and key of the genus Acrophyma Bergroth, 1917.